Soil properties and rhizosphere interactions affecting nitrous oxide emissions with mitigation by nitrification inhibitors in rice growth stages - Zhang, Haipeng; Lu, Yiyin; Li, Wanyi; Liao, Fuxing; Wang, Juanjuan; Zhang, Hongcheng; Yang, Yanju (Frontiers in Plant Science, 2025)
Nitrous oxide (N2O) emissions from paddy soils, particularly from the rice rhizosphere, significantly contribute to agricultural greenhouse gas outputs. This study explores N2O emission dynamics in rhizosphere (R) and non-rhizosphere (NR) soils from two distinct paddy types (JR and YC) during the primary rice growth stages (tillering, jointing, heading, and grain-filling). Cumulative N2O emissions were measured at 688.56, 762.90, 831.20, and 1072.32 µg N kg-1 for JR-NR, JR-R, YC-NR, and YC-R, respectively. Notably, JR-R and YC-R exhibited increases in cumulative N2O emissions by up to 20.04% and 28.23%, respectively, compared to their NR counterparts at different growth stages. These enhanced emissions were primarily associated with microbial genera Nitrosospira and Nitrosospirae, and influenced by factors such as electrical conductivity (EC) and available potassium (AK). The soil organic carbon to total nitrogen ratio (C/N) was a key determinant influencing Nitrosospira abundance. Additionally, nitrification inhibitors (NIs) demonstrated a substantial reduction in N2O emissions, with a decrease of 92.37% in JR-R and 91.93% in YC-R at selected growth stages, showing more pronounced effects compared to NR soils. These findings highlight the efficacy of NIs in significantly mitigating N2O emissions, particularly in rhizosphere soils. Variations in the efficiency of NIs across different soil types and growth stages suggest that optimizing application timing and developing tailored soil-specific strategies could further enhance the effectiveness of NIs in mitigating N2O emissions from paddy fields. This research provides essential insights for developing targeted mitigation strategies to reduce N2O emissions in rice cultivation and contributes to sustainable agricultural practices.